Longitudinal Changes in Circulating Metabolites and Lipoproteins After Breast Cancer Treatment - Giskeødegård, Guro F.; Madssen, Torfinn S.; Sangermani, Matteo; Lundgren, Steinar; Wethal, Torgeir; Andreassen, Trygve; Reidunsdatter, Randi J.; Bathen, Tone F. (Frontiers in Oncology, 2022)
The multimodal treatment of breast cancer may induce long term effects on the metabolic profile and increase the risk of future cardiovascular disease. In this study we characterized longitudinal changes in serum lipoprotein subfractions and metabolites after breast cancer treatment, aiming to determine the long-term effect of different treatment modalities. Further, we investigated the prognostic value of treatment-induced changes on breast cancer-specific and overall 10-year survival. Serum samples from breast cancer patients (n = 250) were collected repeatedly before and after radiotherapy, and serum metabolites and lipoprotein subfractions were quantified by NMR spectroscopy. Longitudinal changes were assessed by univariate and multivariate data analysis methods applicable for repeated measures. Distinct changes were detectable in levels of lipoprotein subfractions and circulating metabolites during the first year, with similar changes despite large differences in treatment regimens. We detect increased free cholesterol and decreased esterified cholesterol levels of HDL subfractions, a switch towards larger LDL particles and higher total LDL-cholesterol, in addition to a switch in the glutamine-glutamate ratio. Non-survivors had different lipid profiles from survivors already at baseline. To conlude, our results show development towards an atherogenic lipid profile in breast cancer patients with different treatment regimens.